Comparative genomics and evolutionary analyses of Sphaeropleales - Xiong, Qian; Zheng, Luqin; Zhang, Qi; Li, Tianli; Zheng, Lingling; Song, Lirong (Frontiers in Plant Science, 2025)
Sphaeropleales is a diverse group with over one thousand species described, which are found in a wide range of habitats showed strong environmental adaptability. This study presented comprehensive genomic analyses of seven newly sequenced Sphaeropleales strains with BUSCO completeness exceeding 90%, alongside comparative assessments with previously sequenced genomes. The genome sizes of Sphaeropleales species ranged from 39.8 Mb to 151.9 Mb, with most having a GC content around 56%. Orthologous analysis revealed unique gene families in each strain, comprising 2 to 3.5% of all genes. Comparative functional analysis indicated that transporters, genes encoding pyrroline-5-carboxylate reductase and antioxidant enzymes played a crucial role in adaptation to environmental stressors like salinity, cold, heavy metals and varying nutrient conditions. Additionally, Sphaeropleales species were found to be B12 auxotrophy, acquiring this vitamin or its precursors through a symbiotic relationship with bacteria. Phylogenetic studies based on 18S rDNA and the low copy othologues confirmed species identification and the relationships inside core Chlorophyta and between prasinophytes. Evolutionary analyses demonstrated all the species exhibited a large count of gene family expansions and contraction, with rapidly evolving and positive selected genes identified in terrestrial Bracteacoccus species, which contributed to their adaptation to terrestrial habitat. These findings enriched the genomic data for Sphaeropleales, particularly the genus Bracteacoccus, which can help in understanding the ecological adaptations, evolutionary relationships, and biotechnological applications of this group of algae.